AN APPRAISAL ANALYSIS : THE INTERPERSONAL MEANINGS IN THE DISCOURSE OF A LYRIC - Yuningsih (English Education Department, 2018)
Lyrics have significant contributions to the music by giving the audience deep understanding about the message contained in the song. The message can be delivered depending on how the writer put the words in the lyrics (Bertoli-Dutra and Bissaco, 2006: 1053). This study focused on analysing interpersonal meanings and linguistics features from the perspective of Appraisal Theory. Due to the time constraints, the study only analysed the interpersonal meaning from Attitude categories, - Affect, Judgement and Affection. The method used was descriptive which data collected from “Lonely Night” song lyric by CNBLUE. The process data analysis was based on Appraisal Framework, a development of Systemic Functional Linguistics, proposed by Martin and White (2005). The result of study showed that the song “Lonely Night” has high Affect sub-categories which reached 81.25%, meanwhile the Judgement and Affection reached the same amount, 9.3%. From all affect types, the song showed unhappiness where the composer revealed the feeling of being dumbed and disrespected. Finally, Appraisal Framework, as one of approach used in many genres, can be used as an alternative for analysing song. Appraisal Framework was developed to make analysis which is more systemic and organized as it was developed from Systemic Functional Linguistics.